2019
DOI: 10.1002/ece3.5912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal precipitation change on soil respiration processes in a seasonally dry tropical forest

Abstract: Precipitation is projected to change intensity and seasonal regime under current global projections. However, little is known about how seasonal precipitation changes will affect soil respiration, especially in seasonally dry tropical forests. In a seasonally dry tropical forest in South China, we conducted a precipitation manipulation experiment to simulate a delayed wet season (DW) and a wetter wet season (WW) over a three-year period. In DW, we reduced 60% throughfall in April and May to delay the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…The annual Rs values in the pretyphoon disturbance years in this study ranged from 5.9 to 9.1 t C ha irrespective of the tree species, which is similar to reported values for other tropical forests [18,19,44,45]. The study results also demonstrated that soil temperature was correlated to Rs for the four tree species in the afforested areas (Figure 4), which is similar to the results for other tropical forests [35,[46][47][48][49][50][51]. However, although the temperature sensitivities of the Rs values (Q 10 ) for the four tree species at the afforested sites were similar to those in other tropical forests [45,52,53], it must be noted that the Q 10 values were significantly lower in the post-typhoon year than in the pretyphoon year (p < 0.05, Table 3).…”
Section: Impact Of Typhoon Disturbances On the Soil Temperature Soil Moisture And Rs Response Of The Four Tree Species At The Afforested supporting
confidence: 88%
See 1 more Smart Citation
“…The annual Rs values in the pretyphoon disturbance years in this study ranged from 5.9 to 9.1 t C ha irrespective of the tree species, which is similar to reported values for other tropical forests [18,19,44,45]. The study results also demonstrated that soil temperature was correlated to Rs for the four tree species in the afforested areas (Figure 4), which is similar to the results for other tropical forests [35,[46][47][48][49][50][51]. However, although the temperature sensitivities of the Rs values (Q 10 ) for the four tree species at the afforested sites were similar to those in other tropical forests [45,52,53], it must be noted that the Q 10 values were significantly lower in the post-typhoon year than in the pretyphoon year (p < 0.05, Table 3).…”
Section: Impact Of Typhoon Disturbances On the Soil Temperature Soil Moisture And Rs Response Of The Four Tree Species At The Afforested supporting
confidence: 88%
“…Extreme climate events such as typhoons alter the patterns of seasonal precipitation, especially in monsoon regions [31], but the scientific understanding of the impact of typhoons on the carbon cycle is still obscure [32]. Typhoons often lead to a large quantity of deposits of green and immature leaves [33,34], and in comparison to natural forests, afforested areas can be more vulnerable to typhoon disturbances [35]. Climate change intensifies typhoon damage to afforested areas and thereby affects Rs.…”
Section: Introductionmentioning
confidence: 99%
“…In a lowland tropical forest, neither N nor P addition increased foliar K concentrations (Santiago et al., 2012). Due to its relatively greater mobility in soil, soil K + leaches in tropical forests with high precipitation (Yu et al., 2020). In our study, we did not observe significant effects of N or P addition on foliar [K] in the tropical forest near the coast (about 5 km), in agreement with a previous study in a Panamanian tropical forest (Santiago et al., 2012), where rain provides enough K to plants.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum SWC values were measured during evening and minimum were during the afternoon because, in most of the days in our measurements, the short and frequent rain events were detected between the late afternoon and early evening measurements. The occurrence of both varying precipitation with the lower and higher rate than the usual has signi cant impacts on SR with the association of ecosystem components in the seasonally dry tropical forest (Yu et al 2020). However, the tropical forests are more sensitive to the changing rainfall than that of the forests in temperate region where the temperature becomes the most prominent in controlling the SR ( Canopy coverage plays a major role to prevent the light from the sun to the under vegetation and suffers from inadequate light intensity in uencing their adaptability and optimum growth by the limitations of nutrient use e ciency.…”
Section: Discussionmentioning
confidence: 99%